Pacific Walkers : Poems - Van Winckel, Nance (Book collections on Project MUSE., 2013)
Nance Van Winckel's wry, provocative slant on the world and her command of images and ideas enliven these stunning poems. Presented in two parts, Pacific Walkers first gives imagined voice to anonymous dead individuals, entries in the John Doe network of the Spokane County Medical Examiner's Records. The focus then shifts to named but now-forgotten individuals in a discarded early-1900s photo album purchased in a secondhand store. We encounter figures devoid of history but enduring among us as lockered remains, and figures who come with histories--first names and dates, and faces preserved in photographs--but who no longer belong to anyone.Watch the trailer: http://www.youtube.com/watch?v=2GtPW3STVX0&list=UUge4MONgLFncQ1w1C_BnHcw&index=10&feature=plcp